Psychiatric consequences of stress after a vehicle accident - Dickov, Aleksandra (Array, 2009)
Vehicle accidents are a common cause of disease and death among people over 30 years of age. Essentially, reaction to stress due to the vehicle accident does not differ from the reaction to other stress factors. There are still no uniform viewpoints about the kind of sequels and their percentage representation after vehicle accidents. Subjects and methods: The research was provided as a prospective study, included 150 subjects who had vehicle accident minimum 2 years prior to the examination. In 87.4% of persons psychiatric consequences last over two years. Long term consequences in 60% of subjects occur as a combination of multiple psychiatric disorders, so the posttraumatic stress disorder and affective disorders never occur one at a time.